Perspektif Hukum terhadap Perlindungan Anak Korban Kekerasan Seksual dalam Undang-Undang Nomor 12 Tahun 2022 - Silvia Cahyadi; Rasji, Rasji (UNES Law Review, 2024)
A nation's legal system must provide for the legal protection of children who are the victims of sexual assault. One of the main initiatives to give children who are victims of sexual assault proper legal protection is Law Number 12 of 2022 about Sexual assault Crimes. This article examines the numerous legal protection measures provided by Law Number 12 of 2022 through a content analysis. These measures include rules pertaining to the definition of sexual violence, court procedures, penalties for offenders, and victim rehabilitation initiatives. The investigation focuses on the potential and difficulties in implementing Law Number 12 of 2022 throughout society, as well as how it offers a thorough legal framework to safeguard the rights of children who are sexually abused.